2015
DOI: 10.20886/jphh.2015.33.4.377-385
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antijamur, Antibakteri Dan Penyembuhan Luka Ekstrak Resin Jernang

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The same occurrence also shown that n-Hexane dragon's blood resin extract at concentration of 15% performed the higher activity against Candida albicans with the diameter of inhibition zone formed of 15.6 mm. This result was in line with the previous study reported by Pasaribu and Totok that states that n-Hexane dragon's blood resin extract has antimicrobial properties with high sensitivity [8]. Pelczar and Chan mentioned that the higher the concentration of the extract, produced the bigger the activity performed in the inhibition zone [16].…”
Section: Antimicrobial Activitiessupporting
confidence: 92%
See 1 more Smart Citation
“…The same occurrence also shown that n-Hexane dragon's blood resin extract at concentration of 15% performed the higher activity against Candida albicans with the diameter of inhibition zone formed of 15.6 mm. This result was in line with the previous study reported by Pasaribu and Totok that states that n-Hexane dragon's blood resin extract has antimicrobial properties with high sensitivity [8]. Pelczar and Chan mentioned that the higher the concentration of the extract, produced the bigger the activity performed in the inhibition zone [16].…”
Section: Antimicrobial Activitiessupporting
confidence: 92%
“…Mohammed states that dragon's blood resin with various solvent extracts such as n-Hexane, Ethyl acetate, Methanol, Acetone and Ethanol have antimicrobial activities against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Candida albicans [7]. The study conducted by Pasaribu revealed that the extracts of n-Hexane, Ethyl acetate, and Methanol of drogon's blood resin have antibacterial and antifungal activities against Staphylococcus aureus, Bacillus subtilis, Candida albicans, and Aspergilus flavus [8].…”
Section: Introductionmentioning
confidence: 99%